2562. Re-Appraisal of Aminoglycoside (AG) Susceptibility Testing Breakpoints Based on the Application of Pharmacokinetics–Pharmacodynamics (PK-PD) and Contemporary Microbiology Surveillance Data. (26th November 2018) - Bhavnani, Sujata M; Onufrak, Nikolas J; Hammel, Jeffrey P; Andes, David R; Bradley, John S; Flamm, Robert K; Ambrose, Paul G; Jones, Ronald N
Abstract: Background: Resistance to AGs and numerous other classes continues to emerge. To ensure that susceptibility is accurately characterized and that clinicians have reliable data to select effective agents, appropriate in vitro susceptibility testing interpretive criteria (susceptible breakpoints [BKPTs]) are crucial to ensure optimal patient care. Recently, USCAST, the USA voice to EUCAST/EMA, evaluated the BKPTs for the 3 most commonly used AGs, gentamicin, tobramycin, and amikacin [Bhavnani et al., IDWeek 2016; P-1977]. As a result of consultation from interested parties, which included evaluating AG dosing regimens provided in the US-FDA product package inserts and simulated patients with varying creatinine clearance, these BKPTS were reassessed. Methods: Data sources considered included longitudinal US reference MIC distributions using in vitro surveillance data collected over 18 years, QC performance (MIC, disk diffusion), population pharmacokinetics (PK), and in vivo PK-PD models. Using population PK models, PK-PD targets for efficacy and Monte Carlo simulation, percent probabilities of PK-PD target attainment by MIC after administration of traditional and extended interval AG dosing regimens were evaluated among simulated patients. Epidemiological cut-off and PK-PD BKPTs were considered when recommending BKPTs for AG–pathogen pairs. Results: An example of PK-PD target attainment analysis output is provided in Figure 1 and a subset of recommended AG BKPTs for 3 pathogens is shown in Table 1. Updated USCAST BKPTs, which were based on the application of population PK and PK-PD models, simulation techniques, and contemporary MIC distribution statistics, are generally lower than those of EUCAST/EMA, USA-FDA, and CLSI. Adequate PK-PD target attainment was not achieved for some AG-pathogen pairs, even when high-dose AG dosing regimens and PK-PD targets for stasis were evaluated (e.g., gentamicin vs. P. aeruginosa ; amikacin vs. S. aureus ). Conclusion: These revised AG BKPT recommendations, which will be made freely available to EUCAST, USA-FDA, and CLSI, will be finalized after considering comments from additional interested stakeholders. This process will be followed in an effort to bring harmonization to global BKPTs for AGs. Disclosures: All authors: No reported disclosures.